Association between caring for grandchildren based on living arrangements and cognitive function among Chinese middle-aged and older adults: The mediating roles of social activities and depressive symptoms - Hou, Xuebei; Xiong, Yuan; Qiao, Guiyuan; Zhou, Jing (Frontiers in Public Health, 2023)
Introduction In the context of an aging population and age-related conditions increasing, the increasing number of middle-aged and older adults are involved in grandchildren care. This study aimed to 1) explore the association between caring for grandchildren based on living arrangements and cognitive function among Chinese middle-aged and older adults; and 2) investigate the mediating roles of social activities and depressive symptoms in the aforementioned association. Methods This study selected 5490 Chinese people (≥45 years old) from the 2018 China Health and Retirement Longitudinal Study (CHARLS). Participants answered questions related to socio-demographics, the Mini-mental State Examination, the intensity of grandchildren care, the Center for Epidemiological Studies Depression Scale, and social activity. Results The results showed that caring for grandchildren and cohabiting with a spouse was positively associated with cognitive function among Chinese middle-aged and older adults (B = 0.829, p < 0.001). Furthermore, there was a positive association between providing intensive or no-intensive grandchildren care and cognitive function. In contrast, caring for grandchildren but not cohabiting with a spouse was negatively associated with cognitive function (B = −0.545, p < 0.05). Moreover, directly and indirectly, caring for grandchildren was significantly associated with cognitive function among Chinese middle-aged and older adults, as mediated by social activities and depressive symptoms. Discussion The findings emphasize that living arrangements, social engagement, and psychological health could be considered when encouraging grandparent care as formal care.